Numerical simulations of triaxial compression tests of cemented sandstone. (September 2019) - Rakhimzhanova, Aigerim K.; Thornton, Colin; Minh, Nguyen Hop; Fok, Sai Cheong; Zhao, Yong
Abstract: Three-dimensional DEM simulations of triaxial compression tests of cemented sandstone samples have been performed at different values of confining pressure, initial density and bond strength. The results show that with increase in bond strength, initial density and confining pressure both the initial stiffness and peak strength increase. For a higher bond strength and initial density the samples exhibit a higher rate of dilation. Bond breakage was found to increase with confining pressure and decrease with bond strength and initial density. The Mohr-Coulomb strength parameters c' and φ' were obtained for the numerical samples and correlations between the shear strength parameters and the bond strength were established. The correlations were then used to find the value of the bond strength to be used for comparisons with results of experimental triaxial tests. The stress-strain responses of the numerical samples were found to be in good agreement with the experimental results. The critical state lines (CSL) of triaxial compression tests for both loose and medium dense systems show that the critical void ratio is independent of the initial density but increases with increase in bond strength. Increasing the bond strength increases the dilation, which leads to a higher critical state void ratio.